Focusing on Health Information: How to Assess Information Quality on the Internet - Haddow, Gaby (2003)
The quality of information on the Internet is extremely variable. For health information, where quality can mean the difference between effective management of a health problem and potentially dangerous treatments, tools to assess quality are imperative. Quality, as a characteristic of information, is discussed in the context of librarianship and health science. The criteria included in quality assessment tools are discussed. An overview of a study using one of these tools is provided to illustrate the importance for library practitioners to have an awareness of quality issues and, more significantly, ways in which Internet users can identify quality health information.